Analysis and Experimental Research of Gear Whine of 2nd Gear of Transmission based on Gear Modification - Zhou Xinjian; Li Guangxing; Mao Le (Jixie chuandong, 2018)
Aiming at the problem of a company dual clutch automatic transmission 2 nd gear whine,a virtual prototype model of the transmission is established by using Romax software. Based on the original simulation results of gear modification parameters,two new designs are proposed,plan A and B,to make sure per unit length load and contact stress concentrated in the center of the gear and the Peak to peak transmission error（ PPTE） values are the minimum. The plan A is to cancel tooth tip relief,plan B is to reduce the helix slope deviation and given the adjustment range,and then the same simulation with the original is carried out. The optimal B is obtained by comparison and analysis of the simulation results of the adjustment range of plan B to be a comparison of plan A. Finally,the NVH experiment of the vehicle is carried out to verify the simulation results of plan A and optimal B. The verification results show that optimal B performs better than plan A by reducing the Sound pressure level（ SPL） obviously and controlling the main order noise 40 d B below under drive conditions through gear modification. The gear whine problem of transmission 2 nd gear is solved eventually,the vehicle NVH performance is improved better.